Implementation of Deep Learning in Islamic Religious Education Learning at SMP Muhammadiyah PK Kottabarat - Gina Rahma Giovanny; Istanto Istanto (Journal of Educational Sciences, 2026)
This study aims to examine the application of the Deep Learning approach in Islamic Religious Education (PAI) learning at SMP Muhammadiyah PK Kottabarat. The research uses a descriptive qualitative method with a case study design. Data collection techniques were carried out through interviews, observations, and documentation of two PAI teachers and students. The results of the research show that the implementation of Deep Learning takes place through three main pillars, namely: (1) meaningful learning, which is realized through the contextualization of PAI material with the real lives of students, (2) mindful learning, which is developed through structured religious activities to foster spiritual awareness and self-reflection, and (3) joyful learning, which is applied through the use of digital technology and interactive learning methods. The research findings reveal that the application of this approach is able to increase student engagement, deepen spiritual understanding, and create meaningful and pleasant learning experiences. The implementation of Deep Learning is supported by internal factors in the form of the openness and adaptive attitude of teachers, as well as external factors in the form of institutional support and infrastructure. The constraints faced include limited learning time and variations in the pedagogical creativity of teachers. This study offers a useful contribution to the progress of Islamic Religious Education teaching that is relevant to the demands of students in the digital era.